2010
DOI: 10.1007/s11103-010-9608-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of DAM5 and DAM6 is suppressed by chilling temperatures and inversely correlated with bud break rate

Abstract: We previously identified a cluster of d ormancy-a ssociated M ADS-box transcription factors (DAM genes) in peach [Prunus persica (L.) Batsch] as potential candidates for control of the non-dormant phenotype observed in the evg mutant. Of these genes, DAM3, DAM5 and DAM6 were winter expressed, suggesting a role for these genes during endodormancy. We used peach cultivars with contrasting chilling requirements (CR) for bud break to observe the expression of DAM3, DAM5 and DAM6 in response to chilling accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 55 publications
12
122
0
Order By: Relevance
“…Based on the experimental results obtained with Japanese apricot (Yamane et al, 2008), we proposed that PmDAM6, an ortholog of PpDAM6, could be one of the internal growth inhibitors that are localized in endodormant buds to prevent buds from resuming growth. The results obtained in this study not only supported our hypothesis that Prunus DAMs could encode dose-dependent negative regulators against bud break but also confirmed the previous indications that PpDAMs were associated with peach terminal bud endodormancy (Jimenez et al, 2010). Furthermore, this study suggested that threshold transcript levels of PpDAM5 and PpDAM6 for inhibiting bud burst differ depending on the cultivars because it appeared that higher PpDAM5 and PpDAM6 transcription levels were required to inhibit bud burst of 'Akatsuki' than 'Okinawa (Tsukuba)'.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the experimental results obtained with Japanese apricot (Yamane et al, 2008), we proposed that PmDAM6, an ortholog of PpDAM6, could be one of the internal growth inhibitors that are localized in endodormant buds to prevent buds from resuming growth. The results obtained in this study not only supported our hypothesis that Prunus DAMs could encode dose-dependent negative regulators against bud break but also confirmed the previous indications that PpDAMs were associated with peach terminal bud endodormancy (Jimenez et al, 2010). Furthermore, this study suggested that threshold transcript levels of PpDAM5 and PpDAM6 for inhibiting bud burst differ depending on the cultivars because it appeared that higher PpDAM5 and PpDAM6 transcription levels were required to inhibit bud burst of 'Akatsuki' than 'Okinawa (Tsukuba)'.…”
Section: Discussionsupporting
confidence: 90%
“…Later, Li et al (2009) demonstrated that PpDAM1, PpDAM2, and PpDAM4 are more closely associated with terminal bud formation than the other three PpDAMs, although all six PpDAMs showed distinct changes in seasonal expression in shoot apex of peach. Furthermore, Jimenez et al (2010) reported that the expression levels of PpDAM5 and PpDAM6 are inversely correlated with the bud break rate of peach terminal buds. Taken together, these results could indicate that PpDAMs are associated not only with endodormancy induction but also with endodormancy release.…”
Section: Introductionmentioning
confidence: 99%
“…In peach, six DAM genes showed distinct seasonal expression changes in the shoot apex. Peach DAM1, DAM2, and DAM4 were most closely associated with terminal bud formation (Li et al, 2009), whereas peach DAM5 and DAM6 expression was negatively correlated with the time required for terminal bud break in peach (Jimenéz et al, 2010). Negative correlation of peach PpDAM5 and PpDAM6 expression with the time required for bud break was also reported for lateral vegetative (Yamane et al, 2011a) and flower (Yamane et al, 2011b, c) buds.…”
Section: ) Identification Of Dormancy-associated Madsbox Genes In Prmentioning
confidence: 76%
“…Secondly, in the early flowering Japanese apricot cultivar 'Taoxingmei', digital expression of DAMs in flower buds was maintained at high levels in ecodormancy (Jan.) in comparison to that observed in endodormancy (Dec.), and decreased during February (Zhong et al, 2013). This is not consistent with the dormancyassociated expression patterns of PmDAMs in vegetative buds (Sasaki et al, 2011) and peach DAMs in flower buds (Jimenéz et al, 2010;Yamane et al, 2011b, c). Recently, chromatin modifications in the peach DAM6 gene were investigated to characterize the repression mechanism of DAM6 expression during dormancy release (Leida et al, 2012).…”
Section: ) Expression Analysis Of Dam Genesmentioning
confidence: 92%
“…Other DAMs, DAM4 and DAM5, were also up-regulated during endodormancy, although statistically significant differences were observed in leaf buds but not in flower buds. This is unlikely to reflect organspecific expression patterns, but probably reflects the lower sensitivity of EST analyses compared with realtime PCR, because it has been reported that DAM5 is up-regulated in flower buds during endodormancy in peach (Jimenéz et al, 2010;Yamane et al, 2011b, c) and Japanese apricot (Ooka et al, 2010). Most of the unigenes that were up-regulated at the endodormant stage, including two commonly up-regulated unique sequences in leaf and flower buds, showed no homology to genes or proteins in the public databases; therefore, we cannot predict their functions, although it is likely that they are involved in endodormancy regulation.…”
Section: Digital Expression Analysis Based On Est Assemblymentioning
confidence: 99%